European Consensus Guidelines on the Management of Neonatal Respiratory Distress Syndrome in Preterm Infants-2010 Update - ÖZEK, EREN (KARGER, 2010)
These updated guidelines contain new evidence from recent Cochrane reviews and the medical literature since 2007. Many of the previous recommendations regarding early surfactant and CPAP are now more firmly evidence-based. The section on delivery room stabilisation has been considerably expanded. There are new recommendations on delaying umbilical cord clamping and a new section has been added on avoiding or reducing duration of mechanical ventilation, including recommendations on caffeine therapy, nasal ventilation, permissive hypercapnia and the role of newer ventilator modalities. A new 'miscellaneous' section has also been added covering aspects of RDS management that arise infrequently.
Keywords: BIRTH-WEIGHT INFANTS; POSITIVE AIRWAY PRESSURE; ELECTIVE CESAREAN-SECTION; PLURALITY-DEPENDENT RISK; 7-YEAR FOLLOW-UP; OXYGEN-SATURATION; PREMATURE-INFANTS; CONTROLLED-TRIAL; SURFACTANT REPLACEMENT; MANDATORY VENTILATION